Prevalence of tuberculosis/HIV coinfection among adults with pulmonary and extrapulmonary tuberculosis in Faculty of Medicine Cairo University Hospitals: a cross-sectional study - Yousri Mohammed Akl; Sabah Ahmed Hussein; Ahmed Abdelmoniem Cordie; Aya Amin Mahmoud; Naglaa Moustafa Mohammed (The Egyptian Journal of Bronchology, 2026)
Abstract Background Pulmonary Tuberculosis (TB) and human immunodeficiency virus (HIV) are closely linked since the emergence of the acquired immunodeficiency syndrome (AIDS). The syndemic relationship between tuberculosis (TB) and HIV remains a critical global health challenge, particularly in resource-limited settings where co-infection complicates diagnosis, treatment, and outcomes. Aim This study aimed to estimate the prevalence of HIV infection among adults diagnosed with pulmonary and extrapulmonary tuberculosis at Cairo University Hospitals. Methods A cross-sectional study was conducted over one year (October 2022 to October 2023) and included 100 adult TB patients who met the inclusion criteria, recruited from both inpatient and outpatient settings. Data collection involved comprehensive history-taking, laboratory investigations for TB diagnosis and performance status assessment. HIV screening was performed using a rapid blood test, with positive cases confirmed by polymerase chain reaction (PCR) and CD4 count measurement. Prevalence was calculated with 95% confidence intervals (CI). Results Among 100 TB patients analyzed, two tested positive for HIV (95% CI: 0.2–7.0%). The mean age of participants was 35.9 ± 14.7 years (range: 18–75 years), and 46% were male. Pulmonary TB accounted for 24% of cases, while 76% had extrapulmonary involvement. Both HIV-positive cases had extrapulmonary TB and CD4 counts < 200 cells/µL. 99% of patients had a good performance status (PS 0–2). Conclusion The prevalence of HIV coinfection among TB patients was low in the study population, it supports continued implementation of routine integrated screening for HIV in TB patients and for TB in people living with HIV to improve early detection and treatment outcome.